Delayed surgical management of rectovaginal fistula: a case report highlighting challenges and lessons learned - Drusany Starič, Kristina; Distefano, Rosario Emanuele Carlo; Campo, Giorgia; Norčič, Gregor (Frontiers in Surgery, 2023)
Background: Rectovaginal fistulas following an obstetric anal sphincter injury's repair are rare in developed country and their management could be challenging, particularly in cases of delayed repair. This study emphasizes the importance of accurately diagnosing and promptly repairing such fistulas for optimal patient well-being.; Case: A 30-year-old patient presented with gas incontinence and a greenish discharge from the vagina, six months after delivering her baby. Examination revealed a small pinhole lesion on the posterior vaginal wall, and an endoanal ultrasound confirmed the presence of a rectovaginal fistula. Surgical repair was delayed for nine months due to the patient's breastfeeding. The fistula was eventually repaired through a transrectal approach, with excision of the fistulous tract and closure of both the rectum and vagina. A laparoscopic protective ileostomy was also performed due to the delayed repair. However, a recurrence of the fistula was detected eight months later, requiring a second repair. The patient underwent physiotherapy for the anal sphincter and achieved optimal sphincter function. After six months, the ileostomy was successfully closed, and the patient remained continent; Conclusions: This case highlights the importance of early recognition and prompt repair of rectovaginal fistulas following obstetric anal sphincter injury. Delayed repairs pose greater challenges and increase the risk of recurrence. Individualized surgical approaches, skilled pelvic floor repair, and a multidisciplinary approach are crucial for successful outcomes. This case underscores the need for careful planning and consideration of patient characteristics in the management of rectovaginal fistulas, aiming to achieve optimal outcomes and patient well-being.